Perinatal Predictors and Mediators of Attachment Patterns in Preschool Children: Exploration of Children's Contributions in Interactions with Mothers - Stefan Kurbatfinski; Jennifer Woo; Henry Ntanda; Gerald Giesbrecht; Nicole Letourneau (MDPI AG, 2024)
Insecure and disorganized attachment patterns in children are linked to poor health outcomes over the lifespan. Attachment patterns may be predicted by variables that influence the quality of children's interactions with their primary caregivers/parents (usually mothers) such as prenatal and postnatal exposures and the children's own behaviours in interactions. The purposes of this exploratory study were to examine: (1) prenatal predictors of children's attachment patterns, and (2) postnatal mediators and moderators of associations between prenatal predictors and children's attachment patterns, with adjustment for relevant covariates. Mother-child dyads (n = 214) from the longitudinal Alberta Pregnancy Outcomes and Nutrition (APrON) cohort were studied using valid and reliable measures. Hayes' mediation analysis was employed to determine direct and indirect effects. Mothers' prenatal cortisol levels directly predicted disorganized (versus organized) child attachment in unadjusted models. Children's passivity (in adjusted models) and compulsivity (in unadjusted and adjusted models) in parent-child interactions mediated the pathway between mothers' prenatal cortisol levels and children's disorganized attachment patterns. Serial mediation analyses revealed that mothers' cortisol levels predicted their children's cortisol levels, which predicted children's compulsivity, and, ultimately, disorganized attachment in both unadjusted and adjusted models. No predictors were correlated with children's insecure (versus secure) attachment. This exploratory research suggests that prenatal exposure to mothers' cortisol levels and children's behavioural contributions to parent-child interaction quality should be considered in the genesis of children's attachment patterns, especially disorganization. Interventions focused on parent-child interactions could also focus on addressing children's behavioral contributions.